Analysis of Factors Affecting the Participation women of childbearing age in Early Detection of Cervical Cancer (Public Health Perspective Journal, 2018)
Cancer disease is a disease with the highest prevalence in Indonesia. In the year 2013 increased to 114 patients and in 2015 a number 115 cervical cancer patients. Cancer often happens to childbearing-age women. The incidence of cervical cancer, in fact, can be suppressed by performing early detection. The purpose of this research is to know the effect of the counseling, husband’s support and information source on early detection of cervical cancer and also the most dominant relative and effective contribution. This research is a quantitative research with cross sectional approach with random sampling technique using three predictor regression analysis. Population and sample in this research are the childbearing-age women in working area of Primary Health Survices Purwodadi I with 80 respondents by using random Sampling technique. The analysis that is used in this research is Regression analysis with 3 predictors. The result of F arithmetic is obtained that F table is based on dk denominator = 3 and dk denominator (80-3-1) = 76. For error level 5% = 2,74 because F count is greater than F table then the correlation coefficient tested is significant that dominant factor is husband’s support. Relative contribution is 73,81% and effective contribution is 64,87%, counseling has 27,5% of relative contribution and 24,17% of effective contribution and information sources have -1,37% of relative contribution and -1,20 of effective contribution. The conclusion of the influence between husband support and counseling on early detection of cervical cancer